(3SaQ GdSYGOI hSajQ GdEaGOIs - (3Yde GdOjf Ydj Hf eMeO GdSNGhj,J (B643 (3g` s ((3efRd GHf GdCHGQ HOQH GdLeGejR (B- (3GdbGgQI s)
(3ChdgG (B:s
(3HGSe Gddg GdPi HGSeg JaJJM GdChGFd gPG cJGH SaQ jJMac HGdeYGfi GdYLjHI hjbac Ydi GdCSQGQ GdZGeVI GdZQjHI s
(3BNQgG (B:s
(3hGdVQJGf GddJGf ZGXJGf MGSOjgG geG GddMeJGf GddJGf JMJ GdEHgGejf , cd hGMOI efgG VQI hgeG MLQ GdWMfhbGd JCHW TQkG Je cJGH SaQ s
(3HgG fXGe GdJYbjHIs
(3fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B332s
Keywords: (3GddZIs